PENGARUH PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS 5 SDN 19 BANDA ACEH - Raudhatul Ismi; Regina Rahmi; Raziska Ibrahimi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model on students’ learning outcomes in the IPAS subject for fifth-grade students at SDN 19 Banda Aceh. The background of this study is based on the low learning outcomes of students caused by teacher-centered learning methods, resulting in low student participation and engagement in the learning process. This research employed a quantitative approach with a pre-experimental design using the One Group Pretest-Posttest Design. The population as well as the sample consisted of all 30 fifth-grade students of SDN 19 Banda Aceh. Data were collected through tests, namely pretest and posttest. The data were analyzed using normality test, N-Gain test, and hypothesis testing (paired sample t-test). The results showed that the data were normally distributed based on the Shapiro-Wilk test, with a significance value of 0.075 for the pretest and 0.082 for the posttest (>0.05). The N-Gain test result indicated an average score of 0.5474, which falls into the medium category, showing an improvement in students’ learning outcomes. Furthermore, the hypothesis test showed a significance value of 0.000 (<0.05), indicating a significant difference between pretest and posttest results. Therefore, it can be concluded that the implementation of the Problem Based Learning model has a significant effect on improving students’ learning outcomes in the IPAS subject for fifth-grade students at SDN 19 Banda Aceh